2018
DOI: 10.18553/jmcp.2018.24.10.1019
|View full text |Cite
|
Sign up to set email alerts
|

Costs Associated with Productivity Loss Among U.S. Patients Newly Diagnosed with Multiple Myeloma Receiving Oral Versus Injectable Chemotherapy

Abstract: BACKGROUND: The use of novel drug agents in the treatment of multiple myeloma (MM) has been associated with improved therapeutic outcomes and survival; however, MM continues to pose a significant economic burden on patients and health care systems. Evaluating economic implications of therapies can provide key points of distinctions between available treatment options. Patients with MM may experience productivity loss, including lost days from work or inability to work due to MM symptoms or to undergoing treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…The ixazomib-based all-oral regimens, including IRd, ICd, and ITd, have demonstrated promising efficacy, safety, and tolerability in rigorously controlled clinical trials for NDMM [ 12 15 , 27 , 28 ]. Besides the greater convenience brought by the oral administration, the NDMM patients who received all-oral regimens have been shown to have lower economic burden of illness, less activity impairment, and lower productivity loss [ 29 ]. These facts together explained the reason for choosing ixazomib-based regimens as frontline therapy in selected real-world patients.…”
Section: Discussionmentioning
confidence: 99%
“…The ixazomib-based all-oral regimens, including IRd, ICd, and ITd, have demonstrated promising efficacy, safety, and tolerability in rigorously controlled clinical trials for NDMM [ 12 15 , 27 , 28 ]. Besides the greater convenience brought by the oral administration, the NDMM patients who received all-oral regimens have been shown to have lower economic burden of illness, less activity impairment, and lower productivity loss [ 29 ]. These facts together explained the reason for choosing ixazomib-based regimens as frontline therapy in selected real-world patients.…”
Section: Discussionmentioning
confidence: 99%
“…Requirements for long-term treatment approaches are summarized in Table 2 9,[14][15][16][17] . The key goals of long-term Table 1 Definitions of therapeutic approaches within the paradigm of long-term treatment.…”
Section: Requirements/goals Of Long-term Treatmentmentioning
confidence: 99%
“…•All-oral regimens have been shown to have lower economic burden of illness, less activity impairment, lower productivity loss, and a trend towards greater convenience than injectable regimens in the frontline setting 15,16 .…”
Section: Requirement Specific Needs For Continuous Therapy and Maintementioning
confidence: 99%
“…Similar productivity loss costs were observed in our study, although we report this equated to an average 168 sickness absence days in the first year after diagnosis in Sweden. Merola et al 49 used an average US salary for all occupations in their estimates, whereas we calculated individual salary losses 31,49 . Another aspect of indirect economic cost to society is state‐funded early pension and, although not covered in this study, warrants further examination.…”
Section: Discussionmentioning
confidence: 95%
“…As age is a key factor in determining ASCT eligibility, workplace sickness absence impacts a minority of the non‐ASCT population; however, patients younger than 66 years of age at diagnosis represented 1269 patients (18% of total non‐ASCT cohort). In a US claims‐based study, Merola et al 49 reported an average 87‐100 days of sickness absence in newly diagnosed MM patients (<66 years old). Similar productivity loss costs were observed in our study, although we report this equated to an average 168 sickness absence days in the first year after diagnosis in Sweden.…”
Section: Discussionmentioning
confidence: 99%